Dioscorea magnibracteata (Dioscoreaceae), a new species from western Ecuador based on the unpublished work of Temple Clayton - Couto, Ricardo Sousa; Cornejo, Xavier (Phytotaxa, 2022)
Dioscorea magnibracteata is described and formally presented as a new species based on specimens identified with unpublished names by Temple Clayton. This species occurs exclusively in the seasonally deciduous dry tropical forest of coastal Ecuador, a fairly threatened environment. This new species is monoecious and features staminate flowers with six stamens but differs markedly from all other species of Neotropical Dioscorea by the staminate inflorescences with very large cymbiform bracts and toothed to lacerated margin. We provide a morphological description as well as information on habitat, geographic distribution and taxonomic comments that include the morphological delimitation of the new species and similarities to other species of Dioscorea sect. Monadelpha.